(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article discusses the discussion - an innovative learning technology in the context of the transition to a personality-oriented education. The influence of the discussion on the student’s personal development is determined by its value-oriented orientation, the creation of favorable conditions for the manifestation of individuality, self-determination in existing points of view on a particular problem, and choice of one’s position. To develop the ability to interact with others, listen and hear others, respect other people’s beliefs, accept an opponent, find common ground, relate and coordinate their position with the positions of other participants in the discussion